Analisa Keandalan Pada Cross Cut Giben - D Daryono (Jurnal Teknik Industri, 2003)
Gatra Mapan Malang Company is a manufacture company that produce crack TV where is part of the production process is using automatic machine. Cross Cut Giben machine is the most important role machine in process of particle cutting that often out of order. So that it is necessary supported with production machine maintenance regularly ang planned.